Association between specific periodontal pathogens, Toll‐like receptor‐4, and nuclear factor‐κB expression in placental tissues of pre‐eclamptic women with periodontitis. Issue 1 (27th March 2017) - Parthiban, Prathahini S.; Mahendra, Jaideep; Logaranjani, Anitha; Shanmugam, Sambandham; Balakrishnan, Anandan; Junaid, Mohammed; Namasivayam, Ambalavanan
Abstract: Aim: The aim of the present study was to determine the association between the presence of specific periodontal pathogens, Toll‐like receptor‐4 (TLR‐4), and nuclear factor‐κB (NF‐κB) expression in the placental tissues of pre‐eclamptic women. Methods: Antenatal periodontal screening was performed in 25 normotensive pregnant women and 25 pre‐eclamptic women. Subgingival plaque and placental tissue samples were collected from both groups and screened for the presence of Porphyromonas gingivalis ( P. gingivalis ), Tannerella forsythia, Aggregatibacter actinomycetemcomitans, and Prevotella intermedia ( P. intermedia ) using real‐time polymerase chain reaction. The placental samples were also analyzed to quantify TLR‐4 and NF‐κB expression. Results: The subgingival plaque samples of pre‐eclamptic women showed significantly higher frequencies of P. intermedia . In the placental samples, P. gingivalis, P. intermedia, and the expression of TLR‐4 and NF‐κB were found to be at significantly higher levels compared to normotensive pregnant women. Using linear regression analysis, the expression of TLR‐4 was significantly influenced by the presence of P. gingivalis (coefficient=3.176, 95% confidence interval [CI]: 367‐5.986) and P. intermedia (coefficient=2.886, 95% CI: 0.77‐5.696), whereas NF‐κB expression was influenced only by the presence of P. intermedia (coefficient=2.220, 95% CI: 0.051‐4.388) in the placental tissues of pre‐eclamptic women. Conclusion: An association exists between P. gingivalis and P. intermedia with increased TLR‐4 and NF‐κB expression in the placenta of pre‐eclamptic women with periodontitis.